A water-soluble membrane for SARS-CoV-2 viral nucleic acid sampling and detection. Issue 43 (3rd November 2021) - Wan, Peng; Cui, Haodong; Zhou, Wenhua; Fu, Wen; Yang, Fan; Wang, Zhongying; Du, Xuemin; Chu, Paul K.; Yu, Xue-Feng
Abstract : This communication describes a novel water-soluble membrane prepared from chitosan intended for SARS-CoV-2 viral nucleic acid collection and detection. Abstract : This communication describes a novel water-soluble membrane prepared from chitosan intended for SARS-CoV-2 viral nucleic acid collection and detection. The CSH membrane formed from nanofibers shows promising potential in the quantitative determination of the SARS-CoV-2 viral nucleic acids at a concentration of 10 2 copies per L in air. The sponge-like structure which allows gas to pass through for collection of viral nucleic acids potentially provides simple, fast, and reliable sampling as well as detection of various types of airborne viruses.